EFEKTIVITAS PENGELOLAAN ALOKASI DANA DESA DALAM MENINGKATKAN PEMBANGUNAN FISIK DESA BANDAR SAUHUR KECAMATAN PURBA KABUPATEN SIMALUNGUN - PAWER PANJAITAN (LP2MTBM MAKARIOZ, 2020)
This study aims to determine the efektivenesess management village allocation in improving physical development in ruralBandar Sauhur south of Purba District of Simalungun in years 2016-2018. And to determine the factors that hinder themanagement of the village fund allocation (ADD) in physical Development in rural Bandar Sauhur. Data were collected withthe documentatiaon and interview. The result showed management through descriptive analysis method using a quantitativeapproach which depict how the efektiveneses village funds allocations from years 2016-2018 referring to be in categoryefeective. The efectivenesess management village funds allocation in physical development in Bandar Sauhur year 2016(100%), 2017 (98%), 2018 (93%). While limiting factors is the comprehension of human resources remain low, misscommunication, and liquefactions the village fund allocation late, the human resources les, and funds less.